(untitled) (Texas Journal of Engineering and Technology, 2024)
Dietary habits of every human impact her or his health. The society-wide situation with regard to the dietary habits is not positive according to the existent surveys, and the same applies to the college students. This paper goal is to identify the dietary habits frequented among the college students at a selected institution (a case study); evaluate the habits; and, propose actions for the institution under review, aimed to positively influence their students’ dietary habits. The paper has been designed as a case study, while the data has been obtained from the evaluation of a quantitative survey (based on an executed questionnaire survey) including the total of n = 219 college students of the selected educational institution. As revealed by the results, there is a statistically significant difference in the students’ dietary habits according to gender and age category.